Navigating the Digital Landscape: An Exploration of the Digital Competence of Indonesian University Students - Fitriah Artina; Karim Suryadi; Iim Siti Masyitoh; Syaifullah Syaifullah; Muhammad Amin (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2025)
Background: The background of this research is based on the rapid development of digital technology, which has transformed the ways students interact, access information, learn, and engage in civic life. Conversely, the role of students as active and reflective digital citizens has not been extensively explored in academic literature.Aims: This research aims to analyze the digital competencies of higher education students in Indonesia, with a focus on how their digital skills support their roles as digital citizens, both in academic contexts and in digital civic participation.Methods: The research employs a quantitative approach using a survey conducted with 145 students from various study programs. The survey instrument measures several dimensions of digital competency, including information literacy, digital research, communication, and engagement on platforms.Results: The results indicate that 85% of students demonstrate a high level of proficiency in the use of information and communication technology (ICT) for academic purposes. However, participation in digital civic activities remains low, with competency levels ranging only from 46.8% to 52.8%. The majority of students exhibit a utilitarian orientation, showing high levels of usage for entertainment and learning (74.8%) but demonstrating moderate competencies in information literacy (74.6%), digital research (67.2%), and digital communication (61.7%).Conclusion: These findings suggest a need for enhanced digital civic education that not only focuses on technical aspects but also aims to develop ethical, creative, and participatory capacities among students as responsible digital citizens.